Corruption in the accounting profession: Survey findings - Krambia-Kapardis, Maria (My University, 2011)
Corruption affects all sectors of the economy. In a recent Harvard Business Review it was mentioned by Professors Nicholas Ambraseys of the Imperial College of London and Professor Roger Bilham of the University Colorado at Boulder that a new assessment of global earthquake fatalities over the past three decades indicates that 83 percent of all deaths caused by the collapse of buildings during earthquakes occurred in countries considered to be unusually corrupt. The two authors have argued that corrupt building practices (e.g. substandard materials, poor assembly methods, inappropriate placement of buildings and non-adherence to building codes) have increased the death toll.